Evaluation on soil charge characteristic and sesquioxide between secondary and rehabilitated forests in UPM Bintulu Campus, Sarawak - Ab Rahman, Mohamad Zawawi (2018)
Conversion of forests into other land use types causes forest degradation. This forest degradation will affect soil structures and fertility. This study was conducted to evaluate and compare the status of charge characteristics and sesquioxides of a rehabilitated and a secondary forest. The soil samples were prepared by previous researchers. Soil samples were collected at two sites, namely a secondary forest and rehabilitated forests. Sampling plot (20x20m) was established at both study sites. In each plot, there were six subplots established, and from that subplots, soil samples were taken from two different soil profiles, i.e. were topsoil (0- 15 cm) and subsoil (15- 30 cm). Soil samples were air-dried and passed through a 2 mm sieve. Soil properties of sesquioxides was determined using Dithionite-Citrate-Bicarbonate (DCB) and Ammonium Oxalate. The DCB method was used to extract the non-crystalline (amorphous) of Al, Fe and Si oxides and hydroxides (Alo, Feo and Sio). The crystalline of Al, Fe and Si oxides and hydroxides was determined using Ammonium oxalate method. The concentrations of extracted Al, Fe and Si were determined by atomic absorption spectroscopy. Charge characteristic properties included Point of Zero Salt Effect (PZSE) and residual charge of PZSE (σρ) was determined using Modified Salt Titration (STPT). Organic matter also determined using Total Organic Carbon (TOC) Analyzer. The results showed the amount of sesquioxides contents was low at all plots in the rehabilitated and secondary forests. This means that the status of soils in the rehabilitated and Nirwana secondary forests had undergone similar highly weathering and leaching. Charge characteristics of PZSE showed that the value mostly was below four at all plots. PZSE and σp in rehabilitated and Nirwana secondary forests did not show clear difference between the plots. This suggests that the former two soils had a relatively similar degree of weathering. Soil fertility was similar in both forests due to similar high weathering process. In conclusion, the soils in rehabilitated and Nirwana secondary forests showed that the forests had undergone high weathering and leaching processes but the low presence of sesquioxides suggested that they were yet to reach the ultimately weathered phase.